Optimization of lemongrass (cymbopogan citratus) essential oil and identification of ITS Bioactive compounds and their biological activity - Liyana binti Yahya (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Diseases such as diabetes mellitus, gout and cancer are among the chronic diseases affecting worldwide population. Presently, there is a growing interest in herbal remedies due to the side effects associated with the use of synthesized conventional treatment available. Therefore an investigation is required to find the alternative approaches to treat these chronic diseases, such as plant based medicine. In this study, lemongrass (Cymbopogan citratus) was chosen and examined on the basis of their usage in traditional medicines throughout Southeast Asia. Optimization process for steam distillation was carried out to examine the optimum conditions of the essential oil extraction. Highest yield of essential oil was obtained from the stalks of lemongrass with the extraction yield of 0.46% (v/v). Through the optimization analysis, the maximum extraction yield could be achieved at the optimum condition of temperature 130o C and extraction time, was seven (7) hours. GCMS analysis revealed the major constituents of the lemongrass essential oil extracted from the stalks and leaves such as citral (neral and geranial), limonene, β-myrcene and geraniol which constitute 67.77% and 67.32% of the total oil respectively. Total phenolic content of the essential oil was also analyzed by Folin and Ciocalteau's phenol reagent and their concentration expressed as Gallic acid equivalent (GAE). The results indicated that all the sample of essential oil gave positive results. Highest amount of phenolic content was obtained from essential oil extracted from lemongrasses stalk, which has phenolic concentration of 2100.769 mg/l GAE, while the lowest concentration of 1846.92 mg/l GAE was obtained from essential oil extracted from lemongrass leaves. Extracted essential oils were then examined for anti oxidant activity by DPPH scavenging test and the highest inhibition was obtained by essential oil extracted from lemongrass stalk (89.5%). β-glucosidase inhibition assay was carried out using an in-vitro model for anti diabetic test. Essential oil extracted from lemongrass stalk showed highest degree of inhibitory activity (89.63%). Anti gout test was examined by xanthine oxidase inhibition (XOI) assay with the maximum percentage of xanthine oxidase inhibition of 81.34% obtained from lemongrass stalk essential oil. Lastly, for the anti cancer activity, stalk essential oil showed the best results among other extracted essential oil which possess the IC50 value at the ratio of 1:6 (volume concentration of essential oil per volume of solvent) when examined with SRB assay. Further analysis should be done in the future to determine the exact compound which can inhibit all the biological assay activities studied in this research. This potential lemongrass essential oil with high positive inhibitory activities can be a potent source for alternative medicine derived from natural sources for treatment of chronic diseases and will also help in reducing the dependence on synthetic drugs in the future.